Evaluation of pork assets in Ecuador: pre and post Covid-19 impact under IAS 41 - Galarza-Alay, Maritza (2024)
This study analyzes the valuation of biological assets in pig production in Ecuador, highlighting the lack of formality in administration and accounting. Despite IAS 41, valuation methods are not standardized. An active market is revealed and, at the same time, an opportunity for professional accountants is identified. This research initially adopts an exploratory nature, since it proceeds to the identification of two essential variables: the valuation of pig biological assets in Ecuador and the application of International Accounting Standard No. 41 (IAS 41). However, it culminates with a mixed methodology: quantitative-descriptive, by carrying out a comparative analysis of the financial statements of four companies (2018 to 2022) with homogeneous characteristics; and qualitative, by analyzing the results of an intentional survey and relating them to the characteristics of the companies under study when categorizing and reporting their biological assets. It is concluded, among other aspects, that the pandemic affected the valuation of biological assets, especially at critical times such as 2020, so there may be uncertainty in the estimation of the fair value of these assets.